FAKTOR FAKTOR YANG MEMPENGARUHI INVOLUSI UTERUS PADA MASA NIFAS DI WILAYAH KERJA PUSKESMAS SIKUMANA - Theresia Mindarsih (STIKes CHMK, 2023)
The puerperium is a time when the female reproductive organs recover to their pre-pregnancy state. Anatomically the condition of the mother's body will experience changes after the birth process, one of which is the return of the uterus to its original size. This process is called uterine involution. This research aims to analyze the factors that influence the process of uterine involution during the postpartum period in the working area of ​​the Sikumanan Health Center, Kupang City.This type of research used an analytic survey with a cohort approach. Univariate and bivariate data analysis. The research sample was 64 people. The sampling technique in this study was purposive sampling, namely 64 post partum mothers at the Sikumana Health Center in August - October 2022. This data analysis used the Chi-Square test with an α value of 0.005. Results: The results of the study showed that 90.6% of the respondents were of a healthy age. The parity of the respondents is mostly a little as much as 68.8%. Most of the education levels are low, 81.2%. The nutritional status of respondents is 64%)/Lila is not KEK. Respondents who did postpartum exercise by 50%.Conclusion: There is a relationship between nutritional status and postpartum exercise with uterine involution (p-value 0.004 , p-value 0.000). There is no relationship between age, parity and education with uterine involution (p-value 1,000, p-value 0.591 and P-value 0.199).Keywords: age, parity, education, nutritional status, uterine involution postpartum exercise.